Влияние высокого давления на получение мелкодисперсных композитов в системе Cалм. – Ti₄WC₅ - Стратийчук, Д. А.; Туркевич, В. З.; Колабылина, Т. В.; Осипов, А. С.; Смирнова, Т. И. (НТУ "ХПИ", 2014)
В данном исследовании в условиях высоких давлений (7,7 ГПа) и температур (1700 – 2100 °С) изучены процессы фазового взаимодействия в квазибинарной системе Cалм. – Ti₄WC₅. Оптимальной температурой формирования прочных связей алмаз-Ti₄WC₅ является 1800 °С. При этой температуре двойной карбид Ti₄WC₅ является стабильным и не распадается согласно данным XRD-анализа. Композит, который показал наиболее высокие физико-механические свойства, содержит около 8 % об. Ti₄WC₅ и может быть рекомендован для использования при камнеобработке.

In this study, the processes of phase interaction in quasi-binary CDiam – Ti₄WC₅ system was studied under high pressure (7.7 GPa) at temperatures (1700 – 2100 С). The optimum temperature of forming of strong bonds of diamond with Ti₄WC₅ is 1800 C. At this temperature binary carbide Ti₄WC₅ is stable and doesn’t decomposed according to data of the XRD-analysis. According to the ultrasound diag-nosis data, the samples of 3.6 g/cm³ density have the following characteristics: Young’s modulus of 902 GPa, the bulk modulus of 340 GPa, Poisson's ratio of 0.082. Microhardness of the composite was HV10 = 51 GPa and KIC = 5.2 MPam1/2. Thermal stability in air was estimated to be about 1100 °C. Thus, it was shown that the binary carbides of refractory metals, in the case of sufficient homogenization of the starting mixture, are promising binders for obtaining of high-strength diamond-containing composites. The ceramic, which shows the highest physical-mechanical properties, comprises about 8 vol. % Ti₄WC₅, and, it can be recommended for use in stone processing.
Effect of high-pressure on the preparation of fine composites in the CDIAM. – Ti₄WC₅ system
Keywords: сверхтвёрдая керамика; алмаз; двойные карбиды; жидкофазное спекание; high-pressure; superhard ceramics; diamond; binary carbides